Peran Tua Terhadap Self Regulated Learning (Kemampuan Kemampuan Belajar) Anak Studi Kasus Pada Masyarakat di Desa Rebalas Krajan Pasuruan - Nurul Hikmah; Abdul Jalil; Achmad Faisol (VICRATINA, 2019)
The results showed that the role of Parents in Guiding the Learning Ability of Children in the Krajan Rebalas Village had a role as educators, protectors, motivators, facilitators and mentors. Based on the results of research conducted around the Krajan Rebalas environment, it can be said that children's learning independence in the environment is included in the moderate level, because based on the research findings that the authors do not all children in the environment are less capable of learning, only a few of them lack of independence in learning. There are 3 conditions for children's learning independence, namely children play more outdoors when night or night time study, children do not ignore parents when told to learn and the influence of community environment such as playmates, socializing and adults around their homes . In addition there are some that can affect the ability of children to be independent when at home, namely gadgets or cellphones, laziness felt by children due to a full day at school and a lot of homework from teachers, friends in the neighborhood around the house, interesting television programs that make children more attractive watching it diminishes is the focus of children's learning independence and the last is that parents too pamper children to give what they want like a mobile.